1962
DOI: 10.1084/jem.116.3.365
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrocortisone on the Response of Fetal Rat Skin in Culture to Ultraviolet Irradiation

Abstract: 1. The effect of hydrocortisone on the development of fetal rat skin in organ culture, and on its repair after exposure to a mixed beam from a mercury lamp, are described. 2. The addition of hydrocortisone (7.5 µg/ml) to the culture medium (HC medium) caused accelerated differentiation and keratinisation of the epidermis followed by atrophic changes as in vivo. 3. Explants were grown for 2 days in either normal or HC medium and then irradiated with light from an Hanovia lamp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1962
1962
1979
1979

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Ultraviolet damage to the skin causes lysosomal membrane rupture and consequent hydrolytic enzyme release (Johnson & Daniels, 1969;Honigsmann, Wolff & Konrad, 1974). Both steroidal and nonsteroidal anti-inflammatory drugs exhibit lysosomal membrane-stabilizing properties (Weissman & Fell, 1962;Ignarro, 1971) that may reduce enzyme release from the lysosomes. Such an effect may play a role in their inhibition of u.v.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet damage to the skin causes lysosomal membrane rupture and consequent hydrolytic enzyme release (Johnson & Daniels, 1969;Honigsmann, Wolff & Konrad, 1974). Both steroidal and nonsteroidal anti-inflammatory drugs exhibit lysosomal membrane-stabilizing properties (Weissman & Fell, 1962;Ignarro, 1971) that may reduce enzyme release from the lysosomes. Such an effect may play a role in their inhibition of u.v.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a coincidence between the in vitro and in vivo actions of vitamin A as a labilizer and cortisol as a stabilizer can conceivably be fortuitous. However, on morphologic grounds, too, protection of lysosomes by glucocorticoids has been shown against hypervitaminosis A in vivo (8,9) and in vitro (10), and against ultraviolet irradiation in vivo (34) and in vitro (35). Desoxycorticosterone acetate was not effective in such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Because of hydrocortisone's effect upon UVL-treated lysosomes, these investigators suggested that this steroid might stabilize intracellular particles against a wide variety of stimuli. Weissmann and Fell (1962) suggested that some of the damage to skin by UVL might be caused by the release of hydrolytic enzymes into the tissue from degenerating cells. Again hydrocortisone was found to reduce and retard the breakdown of cells in skin explants exposed to UVL.…”
Section: B Lysosomesmentioning
confidence: 99%